Association of 25 Hydroxy Vitamin D Levels with Age in Community Acquired Pneumonia - Hina Firdous. Muhammad Rizwan Mahmud, Nadeem Naseem, Sadaf Zaman, Nida Tanveer, Mohammad Ali Khalid, Haider Zaigham Baqai, Hina Firdous. Muhammad Rizwan Mahmud, Nadeem Naseem, Sadaf Zaman, Nida Tanveer, Mohammad Ali Khalid, Haider Zaigham Baqai (Journal of Rawalpindi Medical College, 2019)
Background : To determine association of 25 hydroxy vitamin D deficiency with age in patients with community acquired pneumonia (CAP). Methods: In this descriptive study 150 diagnosed patients of community-acquired pneumonia based on the CURB-65 scoring criteria were enrolled. The 25 hydroxy vitamin D levels were recorded in all patients. Patients were divided into three groups according to their age. Effect modifiers like gender were controlled by stratification. Post stratification chi square test was applied. A p value of 0.05 was considered significant. Results: Mean age of the patients was 40.05 ± 14.33 years (mean ± SD). Out of 150 patients 54.7% (n=82) were males while the 45.3% (n=68) were females. The mean level of vitamin D was 18.43 ± 5.005 (mean ± SD) ng/ml. When the cut off value for deficiency was applied i.e. 20 ng/ml, the 60% (n=90) patients were found deficient while 40% (n=60) patients had normal values. The p value was significant only for the age group to 35 to 50 years. Independent sample t test showed that the difference is statistically significant (p=0.003) in age groups between 35 to 50 years. Conclusions: Lower concentrations of vitamin D might be associated with CAP particularly in age group between 35 to 50 years.